The Environment for Women's Entrepreneurship in the Middle East and North Africa - Chamlou, Nadereh (Washington, DC : World Bank, 2012)
This report is about how women entrepreneurs can contribute more to the quality and direction of economic and social development in the Middle East and North Africa (MENA) region. Economic growth in the Middle East has been remarkable since 2004, mainly because of higher oil prices. Rapid job growth has followed, driven mainly by the private sector. Yet the region still faces two important challenges: the first is to create better jobs for an increasingly educated young workforce; and the second is to diversify its economies away from the traditional sectors of agriculture, natural resources, construction, and public works and into sectors that can provide more and better jobs for young people (sectors that are more export oriented, labor intensive, and knowledge driven). These goals can be achieved only by more innovative and diverse investors. In this, the private sector must play an even bigger role than in the past.